2021
DOI: 10.3389/fonc.2020.632187
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I RNA Editing in Cancer: From Evaluating the Editing Level to Exploring the Editing Effects

Abstract: As an important regulatory mechanism at the posttranscriptional level in metazoans, adenosine deaminase acting on RNA (ADAR)-induced A-to-I RNA editing modification of double-stranded RNA has been widely detected and reported. Editing may lead to non-synonymous amino acid mutations, RNA secondary structure alterations, pre-mRNA processing changes, and microRNA-mRNA redirection, thereby affecting multiple cellular processes and functions. In recent years, researchers have successfully developed several bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 152 publications
2
12
0
Order By: Relevance
“…Among all allelic change features, “A>G,” “C>A,” “C>G,” and “G>A” were retained. Out of which, “A>G” and “G>A” represented A-to-I ( Wang et al, 2021 ) and C-to-U ( Lerner et al, 2019 ) RNA editing events, and their existence had negative impacts on the model output. On the contrary, “C>A” and “C>G” represented RNA-editing exclusive allelic changes that exhibited positive impacts.…”
Section: Resultsmentioning
confidence: 99%
“…Among all allelic change features, “A>G,” “C>A,” “C>G,” and “G>A” were retained. Out of which, “A>G” and “G>A” represented A-to-I ( Wang et al, 2021 ) and C-to-U ( Lerner et al, 2019 ) RNA editing events, and their existence had negative impacts on the model output. On the contrary, “C>A” and “C>G” represented RNA-editing exclusive allelic changes that exhibited positive impacts.…”
Section: Resultsmentioning
confidence: 99%
“…Nm, also called 2′-O-methylation, is the methylation of the 2′ -hydroxyl of ribonucleotides, which is a highly conserved RNA modification in eukaryotes [ 21 ], and it was determined to affect the tumorigenesis of colorectal cancer by regulating rRNA [ 22 ]. Ψ is the transition from uridine to pseudouridine [ 23 ], and A-to-I is the conversion from adenine to inosine [ 24 ]. M 1 A is the methylation of adenosine at position 1, m 7 G is the methylation of guanosine at position 7 [ 25 ], and mcm 5 s 2 U is an important post-transcriptional modification of U34 on specific tRNAs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying novel and e cacious drug targets is urgently needed to expand therapeutic options for lethal PCa. ADAR1-mediated deamination of adenosine-to-inosine (A-to-I) within double-stranded RNA (dsRNA) is the most prevalent form of RNA editing that modi es the sequence of RNA transcripts without changing its genomic blueprints, and its aberration has revealed a close association with autoimmune disease Aicardi-Goutieres Syndrome (AGS), neurodegenerative disease Autism and many kinds of cancer (14,54). Although previous study has reported that PCA3/PRUNE2 axis is mediated by ADAR1 dependent RNA editing effects on tumor growth in AR-dependent prostate cancer cell lines (33), little is known about the role of ADAR1 in AR-negative prostate cancer, and the landscape of A-to-G editing targets in PCa remains underexplored.…”
Section: Discussionmentioning
confidence: 99%